Review on Some Computational Aspects of Boron Neutron Capture Therapy - Liem Peng Hong (Indonesian Journal of Physics and Nuclear Applications, 2018)
This paper reviews some computational aspects of Boron Neutron Capture Therapy (BNCT) with the emphasis on the BNCT treatment planning system. An example of a computational dosimetry system developed in Japan is discussed, particularly, the need of such system for BNCT which uses epithermal neutron beams for non-craniotomy brain tumors as well as head-&-neck cancers. An example of BNCT dose calculation method is also presented.